Ruptura de hematoma hepático secundario a terapia neural homeopática: ¿representa un riesgo para la salud? (2021)
Background: Neural therapy was described in 1925 by brothers Ferdinand and Walter Huneke, as a treatment for headache. Many other scientists made contributions over the years and the therapy continued to be used, however to this day it has not been clarified whether its use is safe for patients. Case report: We present and analyze the case of a patient who was admitted to the emergency room for generalized abdominal pain with 15 days of evolution in whom a hepatic hematoma was diagnosed, an exploratory laparotomy with damage control surgery in the general surgery service was performed, obtaining satisfactory results without complications. In addition, a review of the scientific literature is made. Results and Conclusion: Neural therapy is a pain treatment for which there is not enough scientific evidence to assert its safety in patients, on the contrary it has been shown that it can cause serious complications.